Development of an Intelligent Platform Management controller for the Pulsar IIb - Ramalho, Lucas A. [UNESP]; Paiva, Thiago C. [UNESP]; Iope, Rogerio L. [UNESP]; Leal, Beraldo C. [UNESP]; Liu, Tiehui T.; Olsen, Jamieson; Shinoda, Ailton A. [UNESP]; Vaz, Mario [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
The Pulsar IIb is a general purpose FPGA-based processor board designed for full mesh ATCA backplanes. This hardware was originally designed to support Level-1 silicon track trigger R&D projects at the LHC. Each ATCA carrier board is required to support the Intelligent Platform Management Interface (IPMI) protocol, which is responsible for coordinating hot swap operations and for exchanging sensor data with the shelf manager. This work describes the development of the microcontroller software which supports the IPMI protocol as well as additional non-IPMI services used to remotely program the Pulsar IIb FPGA.